Genome-wide association and linkage mapping strategies reveal the genetic loci and candidate genes of important agronomic traits in Sichuan wheat - Zhi-peng ZHANG; Zhen LI; Fang HE; Ji-juan LÜ; Bin XIE; Xiao-yu YI; Jia-min LI; Jing LI; Jing-han SONG; Zhi-en PU; Jian MA; Yuan-ying PENG; et al. (Journal of Integrative Agriculture, 2023)
Increasing wheat yield is a long-term goal for wheat breeders around the world. Exploiting elite genetic resources and dissecting the genetic basis of important agronomic traits in wheat are the necessary methods for high-yield wheat breeding. This study evaluated nine crucial agronomic traits found in a natural population of 156 wheat varieties and 77 landraces from Sichuan, China in seven environments over two years. The results of this investigation of agronomic traits showed that the landraces had more tillers and higher kernel numbers per spike (KNS), while the breeding varieties had higher thousand-kernel weight (TKW) and kernel weight per spike (KWS). The generalized heritability (H2) values of the nine agronomic traits varied from 0.74 to 0.95. Structure analysis suggested that the natural population could be divided into three groups using 43 198 single nucleotide polymorphism (SNP) markers from the wheat 55K SNP chip. A total of 67 quantitative trait loci (QTLs) were identified by the genome-wide association study (GWAS) analysis based on the Q+K method of a mixed linear model. Three important QTLs were analyzed in this study. Four haplotypes of QFTN.sicau-7BL.1 for fertile tillers number (FTN), three haplotypes of QKNS.sicau-1AL.2 for KNS, and four haplotypes of QTKW.sicau-3BS.1 for TKW were detected. FTN-Hap2, KNS-Hap1, and TKW-Hap2 were excellent haplotypes for each QTL based on the yield performance of 42 varieties in regional trials from 2002 to 2013. The varieties with all three haplotypes showed the highest yield compared to those with either two haplotypes or one haplotype. In addition, the KASP-AX-108866053 marker of QTL QKNS.sicau-1AL.2 was successfully distinguished between three haplotypes (or alleles) in 63 varieties based on the number of kernels per spike in regional trials between 2018 and 2021. These genetic loci and reliable makers can be applied in marker-assisted selection or map-based gene cloning for the genetic improvement of wheat yield.